Role of sex on the efficacy of pharmacological and non-pharmacological treatment of heart failure with reduced ejection fraction: A systematic review - Sanromán Guerrero, María Ascensión; Antoñana Ugalde, Sonia; Hernández Sánchez, Elena; del Prado Díaz, Susana; Jiménez-Blanco Bravo, Marta; Cordero Pereda, David; Zamorano Gómez, José Luis; Álvarez-García, Jesús (Frontiers in Cardiovascular Medicine, 2022)
Background Heart Failure (HF) is a growing epidemic with a similar prevalence in men and women. However, women have historically been underrepresented in clinical trials, leading to uneven evidence regarding the benefit of guideline-directed medical therapy (GDMT). This review aims to outline the sex differences in the efficacy of pharmacological and non-pharmacological treatment of HF with reduced ejection fraction (HFrEF). Methods and results We conducted a systematic review via Medline from inception to 31 January 2022, including all randomized clinical trials published in English including adult patients suffering HFrEF that reported data on the efficacy of each drug. Baseline clinical characteristics, primary outcomes, and sex-specific effects are summarized in tables. The systemic review has been conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement. In total, 29 articles were included in the systematic review. We observed that the proportion of women enrolled in clinical trials was generally low, the absence of a prespecified analysis of efficacy by sex was frequent, and the level of quality of evidence on the efficacy of GDMT and implantable cardioverter defibrillator (ICD) or cardiac resynchronization therapy (CRT-) in women was relatively poor. Conclusions Sex influences the response to treatment of patients suffering from HFrEF. All the results from the landmark randomized clinical trials are based on study populations composed mainly of men. Further studies specifically designed considering sex differences are warranted to elucidate if GDMT and new devices are equally effective in both sexes.